USG guided pigtail catheter placement for drainage of liver abscess as a minimally invasive procedure - Prasanth, Gurijala; Prasad, Ballapalli Hari (International Surgery Journal, 2019)
Background: The objective of the study was to evaluate the advantages of USG guided pigtail catheter placement for drainage of liver abscess as a minimally invasive procedure. Methods: This is a retrospective study conducted in Kamineni Institute of Medical Sciences, Narketpally, Nalgonda, April 2017 to August 2017. It included 45 patients who were diagnosed with solitary liquefied liver abscess. The effectiveness of drainage was determined by doing serial USG scans. Results: Age group varied from 27 to 52 years. Out of 45 patients 41 were men and 4 were women. The male to female ratio was 10:1. All the patients underwent USG guided pigtail catheter insertion for solitary liver abscess. Average hospital stay varied from 2–3 days. No complications were observed during the procedure. Conclusions: This study concludes that drainage of solitary liver abscess by USG guided pigtail placement as a minimally invasive procedure was good in clinically improving the patient’s general condition & decreasing the size of abscess cavity.